Long-Term Surgical Outcome of Trocar Site Hernia Repair. Issue 2 (February 2017) - Kwon, Yoon-Hye; Choe, Eun Kyung; Ryoo, Seung-Bum; Kim, Jeong-Ki; Park, Kyu Joo
Port site hernias are emerging as a problematic complication of laparoscopic surgery. The aim of this study was to elucidate the characteristics of port site hernias and determine the long-term outcomes based on the interval between primary surgery and hernia occurrence. Twenty-four patients were surgically treated for trocar site hernia between 1997 and 2013. The patients were grouped into early-onset group (EOG; less than one month) and late-onset group (LOG; more than one month) based on the interval between laparoscopic surgery and hernia onset. A retrospective analysis was performed. There were seven patients in the EOG and 17 patients in the LOG. The body mass index was significantly higher (P = 0.033) in the LOG. In the EOG, primary closure was performed, and there were no recurrences. In the LOG, mesh reinforcement was applied in 58.8 per cent of patients, and 29.4 per cent of patients had recurrences. This recurrence rate was higher than the recurrence rate after primary repair of incisional hernia after open laparotomy (P = 0.088). In conclusion, In the EOG, small bowel resection was more frequent, but once repaired, there were no recurrences. Although mesh reinforcement was applied in the LOG, the recurrence rate was not less than the EOG.